Demographic assessment of the information literacy competency of freshmen UPCAT passers at the University of the Philippines Los Banos - Ingua, Mary Ann M. (2007)
The study was conducted to assess the information literacy competency of the Freshmen UPCAT passers, in order to examine the relationship between the demographic data and information literacy based on the Association of College & Research Libraries (ACRL) information literacy competency standards for higher education.